Certain Results on Bicomplex Topologies and their Comparison (Global Journal of Science Frontier Research, 2016)
In this paper we have investigated the relation between idempotent order and norm topological structures We have discussed about the relation between real order topology and idempotent order topology and we have also established the relation between real order topology and norm topology
Keywords: real order topology; complex order topology; idempotent order topology; norm topology; comparison